THE IMPACT OF LEARNING STARTS WITH A QUESTION METHOD TO LEARNING OUTCOMES IN (SOCIAL STUDIES) - -, Takiddin; Meidiana, Resty (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
This research aims to know the Effect of Learning Starts With A Question (LSQ) Method to Learning Outcomes of IPS (Social Studies) Subject at MIN 15 Bintaro. The method used in this research is quasi experiment with research design of two group randomized subject pretest and posttest. This research was conducted at MIN 15 Bintaro on 21 April - 12 May 2014. The sampling technique in this study used cluster random sampling. The instrument of this research is a test (multiple choice) which amounts to 25 multiple choice questions. To measure the validity of the data reseacher used Annates Program. After hypothesis testing using technique Paired Sample T-Test obtained t count equal to 0,034 at significance level <0,05, thus, H1 accepted and H0 rejected because 0,034 <0,05, so it can be concluded that there is influence of Â Learning Starts With A Question (LSQ) method to Learning Outcomes of IPS (Social Studies) Subject.